TREND OF INCIDENCE OF GASTRIC CANCER IN SISTAN AND BALUCHESTAN PROVINCE, IRAN - Mohammadian, Maryam; Mahdavifar, Neda; Salehiniya, Hamid (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Gastric cancer is the fifth most common cancer and the third cause of death from cancers in the world and is known as the most deadly cancer in Iran. Since the knowledge about the epidemiological situation and the trend of incidence of this cancer is essential to plan for the prevention and treatment of cancer, this study was performed with the aim of investigating the epidemiological status, the rate and the trend of gastric cancer incidence in Sistan and Baluchestan province. Methods: This study was conducted using existing data and data extracted from the National Cancer Registry System and the Disease Management Center of Iranian Ministry of Health between 2003 and 2008. Age-Standardized incidence rates (ASIR) were calculated using the world standard population. The crude incidence rate was also computed. Cochran–Armitage test for linear trend was used for evaluation of the incidence trend. Results: The number of 255 cases of gastric cancer occurred in the study period that 188 cases were in men and 67 in women. Accordingly, the incidence of gastric cancer has had an ascending trend in Sistan and Baluchestan (p=0.00) and its incidence in men and women has changed to 1.18 and 2.73 in 2004 to 1.84 and 4.48 in 2008, respectively. Furthermore, with ageing, the incidence of gastric cancer has increased in both sexes and its incidence was higher in men than women. Conclusion: The incidence of gastric cancer has an increasing trend in Sistan and Baluchestan, hence, etiological surveys and programs of early diagnosis are useful in this province to the reduce cancer. Keywords: Incidence, Gastric cancer, Iran, Epidemiology.